Effectiveness, Benefits, Determinants, and Limitations of Early Mobilization After General Anesthesia: A Scoping Review - Dermawan, Candra; Rondhianto, Rondhianto; Wijaya, Dodi (Chakra Brahmanda Lentera Institute, 2026)
Background: Early mobilization after general anesthesia is a key component of Enhanced Recovery After Surgery (ERAS) programs that improves postoperative recovery. However, evidence on its effectiveness, limitations, and implementation remains inconsistent across surgical settings. Therefore, this scoping review aimed to map and synthesize the available evidence on the effectiveness, benefits, limitations, and factors influencing the implementation of early mobilization after general anesthesia. Methods: This scoping review followed the Arksey and O'Malley methodological framework and was reported in accordance with the PRISMA-ScR guidelines. Literature searches were conducted in Scopus, PubMed, ScienceDirect, and SpringerLink databases for studies published between 2022 and 2026. A total of 312 records were initially identified. Following duplicate removal, studies underwent title, abstract, and full-text screening based on predefined inclusion and exclusion criteria. Eligible studies included primary research articles involving adult patients undergoing general anesthesia and evaluating early mobilization in perioperative or postoperative settings, whereas review articles, editorials, case reports, and studies unrelated to early mobilization or general anesthesia were excluded. Data were systematically charted using a standardized extraction form, and findings were synthesized using thematic analysis to identify key themes related to effectiveness, benefits, determinants, and limitations of early mobilization. Results: From 312 records initially identified, 250 studies remained after duplicate removal and underwent title and abstract screening. Following full-text assessment, 12 studies met the inclusion criteria and were included in the final synthesis. Thematic synthesis generated four major themes: (1) clinical effectiveness of early mobilization, including improvements in physical function, pain reduction, shortened length of stay, and decreased postoperative complications; (2) physiological and pharmacological determinants influencing mobilization readiness; (3) neurocognitive determinants affecting patients’ ability to participate safely in mobilization; and (4) organizational and healthcare system factors influencing implementation. The review also identified important literature gaps, including the lack of a standardized operational definition of early mobilization, substantial heterogeneity in intervention timing and outcome measures, and limited evidence regarding long-term recovery outcomes. Conclusion: This scoping review suggests that early mobilization after general anesthesia improves postoperative outcomes, including ADL, pain, LOS, and complications. However, evidence remains limited by indirect findings and variability across studies. Future research should evaluate standardized interventions and long-term outcomes in diverse healthcare settings.